Effects of biochar on legume-Rhizobium symbiosis in soil - Khan, Tazeen Fatima; Didar-Ur-Alam, Md (Bangladesh Journal of Botany, 2018)
An in vitro study was conducted to observe the effects of tannery waste and biochar on soil bacterial population particularly legume-Rhizobium symbiosis. The study comprised a total of seven different treatments including a control. Count of total bacteria and Rhizobium was observed on initial materials and on all treated soils. A leguminous plant, cowpea, was used to study the effects on nitrogen fixation which could be further linked to legume-Rhizobium symbiosis. Bacterial population was higher in tannery waste treated soils than the corresponding biochar treated ones. It was found that waste treated soils had higher Rhizobium count than the biochar treated ones. Nitrogen fixation was found to be higher in tannery waste than biochar treatments. Although there appeared to be no adverse impact on legume-Rhizobium symbiosis, growth of bacteria particularly Rhizobium was inhibited indicating that microbial functioning of the soil might be affected and thereby likely to jeopardize agricultural production and food security.